Saccadic function in spasmodic torticollis. Issue 6 (June 1990) - Stell, R; Bronstein, A M; Gresty, M; Buckwell, D; Marsden, C D
Abstract : Twelve patients with idiopathic spasmodic torticollis were compared with 19 normal controls on tests of saccadic eye movements thought to depend upon normal basal ganglia function. The patients were able to make random, predictive, remembered, and self-paced saccades equally as well as control subjects. This suggests that those parts of the basal ganglia which may be damaged in spasmodic torticollis, are separate from pathways responsible for the normal initiation and execution of saccades.